A new discrete macro-element in an analytical platform for seismic assessment of unreinforced masonry buildings. (1st December 2017) - Aghababaie Mobarake, A.; Khanmohammadi, M.; Mirghaderi, S.R.
Highlights: A practical platform for numerical simulation of unreinforced masonry buildings is proposed. The proposed method represents in-plane flexural and shear responses of URM piers and spandrels. Satisfactory prediction of the failure modes, strength, drift and hysteretic behavior. Abstract: This paper proposes a practice-oriented platform for numerical simulation of Unreinforced Masonry (URM) buildings. It is based on introducing a new two-dimensional discrete model compatible with most existing structural analysis softwares. The proposed platform comprises of two individual two-dimensional macro-elements, a basic macro-element for modeling the piers and spandrels and a rigid-interface macro-element for modeling the nodal regions. A complete set of constitutive equations and behavioral specifications is proportionally characterized and discussed for the basic macro-element based on its phenomenology and the past experimental studies. The proposed approach provides a rather simple and efficient platform for linear or nonlinear static and dynamic analyses by considering the in-plane behavior of the URM panels. The validation of the proposed analytical platform is conducted using the results of the past experimental tests on a considerable number of piers, spandrels and a perforated wall. The comparisons indicate that the predicted failure mode and hysteretic behavior as well as the ultimate strength and displacement capacity of these specimens are in a satisfactory agreement. In particular, derivation and interpretation of the results in the proposed approach are straightforward and simple; hence, engineers can use this approach for seismic design or retrofit studies. The proposed platform can be further developed and effectively used for modeling a large building or numerous buildings.